Correlations between dimensions of work motivation and dimensions of job satisfaction of employees in hotels and travel agencies - Nedeljković-Knežević Milena; Škorić Jelena; Mijatov Maja (Marketing (Beograd. 1991), 2019)
Rapid development of service sector at global level prompted many researchers to examine specifics of work in this sector. One of specifics is so-called service meeting. During the service meeting there is an emotional exchange between provider and customers, so the work motivation and satisfaction of employees is important for perception of the high quality of delivered service by consumers. Subject of this paper is related to development of internal marketing in order to determine correlations between dimensions of job satisfaction and dimensions of motivational potential of the job, as important aspects of gaining the customers' satisfaction, according to the Hackman-Oldham model in selected hotels and travel agencies in Belgrade and Novi Sad. According to this model, five basic characteristics of the job (diversity of work, identity of the task, importance of the task, autonomy and feedback) are antecedents of work motivation and job satisfaction. Using the Hackman-Oldham theory, one needs to find out the extent to which the job in hotel and travel agency contains aforementioned basic characteristics, or whether the jobs in these two sectors have motivational potential. The aim of the paper is to provide recommendations for development of internal marketing on the basis of increasing the employees' work motivation and their job satisfaction in different organizations that are operating in service sector (tourism and hospitality), in order to provide services of high quality and to gain the customers' satisfaction.